1992
DOI: 10.1021/je00008a026
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate dissociation pressures for methane or ethane in the presence of aqueous solutions of triethylene glycol

Abstract: Hydrate dissociation pressures for methane or ethane contacting aqueous solutions of triethylene glycol have been measured in the temperature range 273-294 K. A simple measurement technique is described which utilizes a high-pressure visual cell and is believed to be inaccurate to ±0.25 MPa in general, increasing to ±0.5 MPa at higher pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…for all of 57 data points was found to be 2.5 per cent with a maximum error of 5.82 per cent. The maximum error was found at T = 273.16 K and (25) pressure for methane hydrate formation conditions in triethylene glycol solutions plotted against temperature. , pure water; ♦, TEG20; , TEG40; -, predicted.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…for all of 57 data points was found to be 2.5 per cent with a maximum error of 5.82 per cent. The maximum error was found at T = 273.16 K and (25) pressure for methane hydrate formation conditions in triethylene glycol solutions plotted against temperature. , pure water; ♦, TEG20; , TEG40; -, predicted.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 1 shows the methane hydrate dissociation pressures in aqueous solutions containing electrolytes. Using the proposed model, the a.a.p.e.s for the prediction of (25,26) pressure for methane hydrate formation conditions in aqueous solutions containing electrolytes plotted against temperature. , pure water; ♦, Na3; , Na3K3; , Na5K5; •, Na10Ca3; •, Na6Ca10; , Na10K12; -, predicted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out for investigating the equilibrium conditions of gas hydrate in the presence of inhibitors [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Thereof, Ross and Toczylkin [80] investigated the behaviors of hydrate dissociation pressures for methane or ethane containing aqueous triethylene glycol with an isothermal apparatus. Englezos and Bishnoi [82], Englezos [83], Hutz and Englezos [84] studied gas hydrate formation/decomposition behaviors in electrolyte solutions.…”
Section: Chemical Injection Methodsmentioning
confidence: 99%
“…This experimental data could be of interest for developing predicting tools with the aim of studying the hydrate stability zones of sour reservoir fluids. So far, hydrate dissociation data were reported by different authors for various gases: Ross and Toczylkin (1992) reported experimental dissociation conditions of methane and ethane hydrates in the presence of TEG aqueous solutions. Later, Servio and Englezos (1997) measured and reported hydrate dissociation conditions of propane in the presence of TEG aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%